Towards a companion system for collision avoidance during robot-assisted needle placement - Currle, Eva; Hemm, Johannes; Schäfer, Armin; Beckerle, Philipp; Horsch, Johannes; Stallkamp, Jan; Kühne, Markus (Current Directions in Biomedical Engineering, 2021)
Robotic assistance systems for surgery enable fast and precise interventions with reduced complication rates. However, these benefits are accompanied by a more complex operating room (OR) and the risk of collision with robotic assistance systems. Current strategies for collision avoidance and minimizing possible injuries require the adaptation of robotic trajectories and a computational model of the surroundings. In contrast, this work presents a novel companion system for collision avoidance without influencing robotic trajectories. The companion system consists of a preoperative planning application and an augmented reality application for intraoperative support. The companion system visualizes the workflow within the OR and allows robot movements to be seen virtually, before they are executed by the actual robotic assistance system. Preliminary experiments with users imply that the companion system leads to a positive user experience, enables users to follow a predefined workflow in the OR, but requires further refinement to improve accuracy for practical collision avoidance.
CRIS-Team Scopus Importer:2021-09-17
Keywords: augmented reality; collision avoidance; companion system; hybrid OR; robot-assisted surgery